Development of an Interactive E-Module Using a PBL Approach to Static Electricity Materials to Improve Students' Critical Thinking Skills - Sitti Maryani; Pariabti Palloan; Khaeruddin (Jurnal Penelitian Pendidikan IPA, 2026)
This research is a type of research and development (R&D) using the 4D model: define, design, develop, and disseminate. The goal of this research and development is to find out the content validity, practitioners’ responses, and the effectiveness of using an interactive e-module with a Problem-Based Learning (PBL) approach in physics learning to improve students’ critical thinking skills. The content validity of the e-module was evaluated by experts and tested using Aiken’s V. Its practicality was evaluated by 10 physics teachers from South Sulawesi. The e-module was tested on 19 students in class XII B at MAN Kabupaten Kepulauan Selayar. The instruments used in this study included a validation sheet for the e-module, a validation sheet for the practitioners’ response questionnaire, and a critical thinking test validation sheet. Each instrument was validated by experts. The practitioners’ questionnaire and the critical thinking test were also used in the study. The results showed that the PBL-based interactive e-module in physics learning was valid according to the experts, highly practical according to the practitioners’ responses, and effective in improving students’ critical thinking skills, with an N-gain percentage of 57,71%. Based on the results, the developed e-module is considered valid, practical, and effective in improving students’ critical thinking skills.